Real World Digital Video, Second Edition - Shaner, Pete; Jones, Gerald (Peachpit Press, 2004)
You never thought you'd be shooting a corporate training video as part of your job as HR manager, but, well here you are--with a camcorder, a directive, and not a clue how to begin! You--and the many people who find themselves in similar situations--need this volume! Realizing that you're expected to provide professional results regardless, the authors of this volume dig deep into every phase of the DV production process: from capturing images and sound to editing, post-processing, adding special effects, and distributing the final product. Special emphasis is placed on the industrial-strength techniques that will get you up to speed quickly on the hardware and software advances that have occurred since the last edition. You'll find new sections on shooting and post-processing film-look (24p) and HDTV video, as well as special coverage of the latest eye-popping special effects. A companion DVD includes demo video clips, award-winning short films, interviews with DV pros, and lots more goodies.